Simulation and analysis of 3D-printed flexure mechanisms - Kwek Muhammad Danial Bakhtiar (2019)
With the existing extensive research conducted on compliant mechanism, it can now render new and advance answers to various mechanical design enigmas. Hence, compliant mechanism has been growing increasingly in microelectromechanical systems (MEMS) due to its ability in reducing cost yet increasing performance simultaneously. The reason is that compliant mechanism deviates away from conventional rigid-link mechanisms because it involves mobility from the deflection of its flexure members than just movable joints only. Besides, with compliant mechanism requiring lesser movable joints results in an increase of mechanism precision as backlash may be reduced or eliminated. In this report, a simulation comparison between three compliant models were executed through a Finite Element Analysis (FEA) software, ANSYS Workbench. The three models were designed through different design methods that are discussed in the literature review. After which, one of the designs was selected to be fabricated to exhibit the desired motions. The prototype presents a 3-DOF - - compliant mechanism that was intended for optimal stiffness performance, delivering an outstanding translational and rotational stiffness ratio of 520 and 1570 respectively and a large workspace of ±6.31mm x 7.57° x 7.28°.